Do or Die - Brockmann, Suzanne; Lawlor, Patrick G. (Patrick Girard); Ewbank, Melanie; Blackstone Audio, Inc. ([Ashland, Oregon] : Blackstone Audio, Inc., 2014)
Navy SEAL Ian Dunn went rogue, or so the world has been led to believe. In reality, he's still fighting for good, leading a small band of operatives who 'unofficially' take care of high-stakes deals. The U.S. government wants Ian to breach an embassy and rescue a pair of kidnapped children. Ian's beautiful new attorney Phoebe is determined to free them, and insists she go along. Intense feelings grow between them as they gear up, and they will do whatever it takes to save the kids-or die trying.
Keywords: Kidnapping -- Fiction; Spy stories; Man-woman relationships -- Fiction; Audiobooks; South America -- Fiction; Romantic suspense fiction; Suspense fiction; Audiobooks